The fountain - Milchan, Arnon; Smith, Iain.; Watson, Eric.; Aronofsky, Darren; Handel, Ari.; Jackman, Hugh.; Weisz, Rachel, 1971-; Burstyn, Ellen, 1932-; Margolis, Mark.; McHattie, Stephen; Hernandez, Fernando; Curtis, Cliff, 1968-; et al. (Burbank, CA : Warner Home Video, 2007)
Yesterday, today, tomorrow. Past, present, future. Through time and space, one man embarks on a bold 1,000-year odyssey to defeat humankind's most indomitable foe, death. Tom is a man who is devoted to one woman, Izzi, and becomes determined to protect her from forces that threaten her existence. His quest leads him to 16th century Europe and America where Tomas is a Spanish explorer searching for Incan magic; to the present day where Tom is a doctor attempting to cure his dying wife; to the 26th century where Tommy is a space traveler seeking a gateway to the afterlife.
English track: Dolby digital 5.1.
Title from container.
Originally released as a motion picture in 2006.
Special features: 'Inside The fountain : death and rebirth'; gallery of 6 featurettes exploring the movie's various periods and settings; theatrical trailer.
Director of photography, Matthew Libatique ; editor, Jay Rabinowitz ; music, Clint Mansell ; costume designer, Reně April ; production designer, James Chinlund ; visual effects supervisor, Peter Oberdorfer.
Hugh Jackman, Rachel Weisz, Ellen Burstyn, Mark Margolis, Stephen McHattie, Fernando Hernandez, Cliff Curtis, Sean Patrick Thomas, Donna Murphy, Ethan Suplee.
Keywords: Time travel -- Drama; Women and death -- Drama; Love -- Drama; Man-woman relationships -- Drama; Explorers -- Drama; Space travelers -- Drama; Action and adventure films; Films for the hearing impaired; Feature films; Action and adventure films; Fantasy films; Love stories; Science fiction films